DYNAMICS OF PREDATOR-PREY TYPE OF SYSTEM WITH NONMONOTONIC RESPONSE FUNCTION AND PERIODIC PERTURBATION - (NIM: 30110009), ERIC
Broer et al in (Broer dkk., 2005; Broer dkk., 2006; Broer dkk., 2007) discusses the bifurcation analysis of predator-prey system with nonmonotonic response function thoroughly. He found several results in codimension three bifurcation acts as an organizing center. In this thesis, we will add periodic perturbation at the carrying capacity term. As we have already known, the periodic perturbation change the equilibrium of the system to a periodic solution. In the new system, we found new bifurcations, i.e. new torus and fold. We also give reasoning on the occurence of strange attractor in this system.